Preparation method of carbon nano tube porous high-thermal-conductivity intermediate layer suitable for brazing
The carbon source is loaded on the surface of the foam copper by hydrothermal method and annealing, which solves the problem of uneven catalyst distribution in carbon nanotube growth, and achieves uniform growth and high thermal conductivity of carbon nanotubes, which is suitable for the preparation of brazed intermediate layers.
Patent Information
- Application Number
- CN202510022149.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The growth of carbon nanotubes on the existing foamed copper intermediate layer has excessive or uneven distribution of catalysts, resulting in poor adhesion and low thermal conductivity of carbon nanotubes.
The carbon source is loaded by hydrothermal method, and a uniform carbon precursor is formed on the surface of the foam copper foam through the glucose solution, and annealed under the conditions of 550°C to 750°C. The spontaneous transfer of the foam copper substrate is used to grow in situ to generate fine carbon nanotubes.
The uniform growth and strong adhesion of carbon nanotubes are achieved, the thermal conductivity of foamed copper is improved to 28W/m·K, the use of precious metal catalysts is avoided, the process cost is reduced, and it is suitable for batch and industrial production.
Smart Images

Figure CN119750557A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a brazing intermediate layer. Background Art
[0002] Growing carbon nanotubes (CNTs) on the copper foam interlayer has important research significance and application value. Its purpose is to utilize the excellent thermal conductivity, electrical conductivity and mechanical properties of carbon nanotubes to further improve the comprehensive performance of copper foam, so as to meet the needs of high-performance brazing joint materials. As a metal material with high porosity and excellent thermal conductivity, copper foam is often used as a brazing interlayer to achieve efficient connection between different materials. However, copper foam may face problems such as insufficient thermal conductivity and unstable mechanical properties in practical applications, which limits its wide application in the field of high thermal conductivity and precision connection.
[0003] By growing uniformly distributed carbon nanotube arrays on the surface of copper foam, the thermal conductivity and interfacial bonding strength of copper foam can be further enhanced, and its performance in brazing applications can be improved. At present, chemical vapor deposition (CVD), laser discharge and arc discharge methods have been widely used to prepare carbon nanotube arrays, but their process is complicated and costly. In the process of using catalysts to promote the growth of carbon nanotubes, the growth quality of carbon nanotubes is often significantly affected by the dispersion, size and morphology of the catalyst. Therefore, selecting and optimizing the catalyst becomes the key to achieving high-quality and uniformly distributed carbon nanotube arrays. When growing carbon nanotubes in copper foam, the bonding quality between the catalyst and the substrate directly determines the adhesion and growth efficiency of the carbon nanotubes, and also affects the thermal conductivity and mechanical properties of the composite material. By achieving good bonding with carbon nanotubes on the copper foam intermediate layer, the thermal conductivity, mechanical strength and electrical properties of the brazed joint can be significantly improved. However, there are still problems such as uneven catalyst distribution and poor adhesion of carbon nanotubes in existing studies. It is urgent to further optimize the preparation process to achieve high performance and reliable application of copper foam-carbon nanotube composites. Summary of the invention
[0004] The present invention aims to solve the problem that the growth of carbon nanotubes on the existing foam copper intermediate layer has excessive or uneven catalyst distribution, resulting in poor adhesion and low thermal conductivity of the carbon nanotubes, and further provides a method for preparing a porous high thermal conductivity carbon nanotube intermediate layer suitable for brazing.
[0005] A method for preparing a porous carbon nanotube high thermal conductivity intermediate layer suitable for brazing is carried out according to the following steps:
[0006] 1. Using hydrothermal method to load carbon source:
[0007] ① Dissolve glucose in deionized water and stir evenly at room temperature to obtain a glucose solution;
[0008] ② Immerse the copper foam in glucose solution for high temperature and high pressure reaction;
[0009] ③ After high temperature and high pressure reaction, cooling to room temperature, a foam copper loaded with carbon source is obtained;
[0010] 2. Annealing at high temperature:
[0011] Under the conditions of protective atmosphere and temperature of 550°C to 750°C, the foam copper loaded with the carbon source is kept warm for 4h to 5h, and finally taken out after being cooled in the furnace to obtain a porous high thermal conductivity middle layer of carbon nanotubes, thus completing the preparation method of the porous high thermal conductivity middle layer of carbon nanotubes suitable for brazing.
[0012] The beneficial effects of the present invention are:
[0013] 1. Enhanced adhesion and high thermal conductivity: Through the method of hydrothermal glucose solution, the product is covered on the surface of the copper foam and annealed at high temperature to generate fine carbon nanotubes. The main reason for its growth is that after the hydrothermal reaction, the surface of the copper foam is evenly coated with a carbon layer, and Cu diffuses from the substrate material to the surface and transfers to the carbon layer in the form of nano-copper balls. The nano-copper balls are evenly distributed to form a densely arranged catalytic array. The Cu nano-balls are used as catalysts for the growth of carbon nanotubes, providing a guarantee for the uniform growth of carbon nanotubes. Under the catalytic action of the Cu nano-balls, they recrystallize and grow into carbon nanotubes with regular structures. Through the spontaneous transfer in-situ growth of the copper foam substrate, the adhesion is stronger, and the prepared carbon nanotube porous high thermal conductivity intermediate layer has excellent thermal conductivity, reaching 28W / m·K.
[0014] 2. No need for additional catalysts: Traditional methods usually rely on precious metal catalysts (such as iron, cobalt, and nickel) to promote the growth of carbon nanotubes. This method uses the catalytic effect of the foam copper substrate itself to achieve the generation of carbon nanotubes through an annealing process, avoiding the catalyst preparation and deposition steps, simplifying the process flow, reducing costs, and reducing the pollution problems that may be caused by metal residues.
[0015] 3. Low temperature requirement: This method first forms a uniform carbon precursor on the substrate through a hydrothermal reaction, and then annealing at a relatively low temperature of 550℃ to 750℃ to grow carbon nanotubes, while traditional methods such as chemical vapor deposition (CVD) usually require a high temperature environment of 800℃ to 1000℃. The lower annealing temperature not only saves energy, but also reduces the risk of deformation, oxidation or damage of the substrate material due to high temperature, which is particularly suitable for processing heat-sensitive or complex structure substrates, such as foam copper.
[0016] 4. Simple and controllable process: The hydrothermal method has mild conditions and is easy to operate. By adjusting parameters such as the concentration of the glucose solution, reaction time and temperature, the morphology and distribution of the carbon precursor can be precisely controlled, thereby achieving high coverage and uniform distribution of carbon nanotubes on the substrate surface. This high controllability helps optimize the structure and performance of carbon nanotubes and improve the quality and consistency of the final product.
[0017] 5. Applicable to complex geometric structures: The surface of copper foam has a three-dimensional porous network structure. The traditional vapor deposition method easily forms non-uniform coating on complex geometric surfaces, while the hydrothermal method uses liquid phase reaction to allow the glucose solution to fully infiltrate the substrate surface and pores, ensuring uniform deposition of the carbon precursor. In the subsequent annealing process, carbon nanotubes can also form a uniform growth distribution on the entire network structure.
[0018] 6. No by-product pollution: The hydrothermal method uses glucose as a carbon source, which is non-toxic and harmless, and produces almost no harmful gases or by-products during the reaction. Compared with traditional carbon nanotube growth methods (such as using gaseous carbon sources such as methane and acetylene, which may release toxic by-products), this process is more environmentally friendly and safer.
[0019] 7. Suitable for batch production and industrialization: The hydrothermal reaction has good scalability and can process multiple samples at the same time. Combined with the low-temperature annealing process, this method has high economy and operability in batch production and is more suitable for industrial application. With its advantages of green environmental protection, low cost, high efficiency and easy operation, this process provides an innovative and practical technical route for the growth of carbon nanotubes on the surface of copper foam, which is particularly suitable for the preparation of composite materials in the fields of thermal conductivity, heat dissipation and energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the carbon nanotube porous high thermal conductivity intermediate layer prepared in Example 1;
[0021] Figure 2 This is a transmission electron microscope energy spectrum of the nano copper ball catalytic array in the carbon nanotube porous high thermal conductivity middle layer prepared in Example 1;
[0022] Figure 3 This is a digital photo of the carbon nanotube porous high thermal conductivity intermediate layer prepared in Example 1;
[0023] Figure 4 This is an enhanced Raman curve of the carbon nanotube porous high thermal conductivity intermediate layer prepared in Example 1. DETAILED DESCRIPTION
[0024] Specific implementation method 1: This implementation method is a method for preparing a porous high thermal conductivity carbon nanotube intermediate layer suitable for brazing, which is carried out according to the following steps:
[0025] 1. Using hydrothermal method to load carbon source:
[0026] ① Dissolve glucose in deionized water and stir evenly at room temperature to obtain a glucose solution;
[0027] ② Immerse the copper foam in glucose solution for high temperature and high pressure reaction;
[0028] ③ After high temperature and high pressure reaction, cooling to room temperature, a foam copper loaded with carbon source is obtained;
[0029] 2. Annealing at high temperature:
[0030] Under the conditions of protective atmosphere and temperature of 550°C to 750°C, the foam copper loaded with the carbon source is kept warm for 4h to 5h, and finally taken out after being cooled in the furnace to obtain a porous high thermal conductivity middle layer of carbon nanotubes, thus completing the preparation method of the porous high thermal conductivity middle layer of carbon nanotubes suitable for brazing.
[0031] The beneficial effects of this embodiment are:
[0032] 1. Enhanced adhesion and high thermal conductivity: Through the method of hydrothermal glucose solution, the product is covered on the surface of the copper foam and annealed at high temperature to generate fine carbon nanotubes. The main reason for its growth is that after the hydrothermal reaction, the surface of the copper foam is evenly coated with a carbon layer, and Cu diffuses from the substrate material to the surface and transfers to the carbon layer in the form of nano-copper balls. The nano-copper balls are evenly distributed to form a densely arranged catalytic array. The Cu nano-balls are used as catalysts for the growth of carbon nanotubes, providing a guarantee for the uniform growth of carbon nanotubes. Under the catalytic action of the Cu nano-balls, they recrystallize and grow into carbon nanotubes with regular structures. Through the spontaneous transfer in-situ growth of the copper foam substrate, the adhesion is stronger, and the prepared carbon nanotube porous high thermal conductivity intermediate layer has excellent thermal conductivity, reaching 28W / m·K.
[0033] 2. No need for additional catalysts: Traditional methods usually rely on precious metal catalysts (such as iron, cobalt, and nickel) to promote the growth of carbon nanotubes. This method uses the catalytic effect of the foam copper substrate itself to achieve the generation of carbon nanotubes through an annealing process, avoiding the catalyst preparation and deposition steps, simplifying the process flow, reducing costs, and reducing the pollution problems that may be caused by metal residues.
[0034] 3. Low temperature requirement: This method first forms a uniform carbon precursor on the substrate through a hydrothermal reaction, and then annealing at a relatively low temperature of 550℃ to 750℃ to grow carbon nanotubes, while traditional methods such as chemical vapor deposition (CVD) usually require a high temperature environment of 800℃ to 1000℃. The lower annealing temperature not only saves energy, but also reduces the risk of deformation, oxidation or damage of the substrate material due to high temperature, which is particularly suitable for processing heat-sensitive or complex structure substrates, such as foam copper.
[0035] 4. Simple and controllable process: The hydrothermal method has mild conditions and is easy to operate. By adjusting parameters such as the concentration of the glucose solution, reaction time and temperature, the morphology and distribution of the carbon precursor can be precisely controlled, thereby achieving high coverage and uniform distribution of carbon nanotubes on the substrate surface. This high controllability helps optimize the structure and performance of carbon nanotubes and improve the quality and consistency of the final product.
[0036] 5. Applicable to complex geometric structures: The surface of copper foam has a three-dimensional porous network structure. The traditional vapor deposition method easily forms non-uniform coating on complex geometric surfaces, while the hydrothermal method uses liquid phase reaction to allow the glucose solution to fully infiltrate the substrate surface and pores, ensuring uniform deposition of the carbon precursor. In the subsequent annealing process, carbon nanotubes can also form a uniform growth distribution on the entire network structure.
[0037] 6. No by-product pollution: The hydrothermal method uses glucose as a carbon source, which is non-toxic and harmless, and produces almost no harmful gases or by-products during the reaction. Compared with traditional carbon nanotube growth methods (such as using gaseous carbon sources such as methane and acetylene, which may release toxic by-products), this process is more environmentally friendly and safer.
[0038] 7. Suitable for batch production and industrialization: The hydrothermal reaction has good scalability and can process multiple samples at the same time. Combined with the low-temperature annealing process, this method has high economy and operability in batch production and is more suitable for industrial application. With its advantages of green environmental protection, low cost, high efficiency and easy operation, this process provides an innovative and practical technical route for the growth of carbon nanotubes on the surface of copper foam, which is particularly suitable for the preparation of composite materials in the fields of thermal conductivity, heat dissipation and energy.
[0039] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the concentration of the glucose solution in step 1① is 0.1 mol / L to 1 mol / L. The rest is the same as the specific implementation method 1.
[0040] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: the number of pores per inch (PPI) of the foam copper in step 1② is 90 to 100. Other aspects are the same as specific implementation method 1 or 2.
[0041] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the high temperature and high pressure reaction described in step 1② is specifically carried out at a reaction temperature of 180°C to 200°C and a pressure of 5MPa to 10MPa for 3h to 6h. The rest is the same as specific embodiment 3.
[0042] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the high temperature and high pressure reaction described in step 1② is specifically carried out at a reaction temperature of 180°C to 200°C and a pressure of 5MPa to 10MPa for 6h. The rest is the same as specific embodiments 1 to 4.
[0043] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the protective atmosphere in step 2 is one of argon, hydrogen and nitrogen or a mixed gas of several of them. The rest is the same as specific embodiments 1 to 5.
[0044] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that the gas flow rate of the protective atmosphere in step 2 is 50 sccm to 80 sccm. The rest is the same as specific embodiments 1 to 6.
[0045] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: in step 2, the carbon source-loaded copper foam is heated to 550° C. to 750° C. at a heating rate of 5° C. / min to 15° C. / min under a protective atmosphere. Other aspects are the same as specific embodiments 1 to 7.
[0046] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 2, under a protective atmosphere, the carbon source-loaded copper foam is heated to 600° C. to 750° C. at a heating rate of 5° C. / min to 10° C. / min. The rest is the same as specific embodiments 1 to 8.
[0047] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that in step 2, the carbon source-loaded copper foam is kept warm for 4 to 5 hours under a protective atmosphere at a temperature of 600° C. to 750° C. The rest is the same as specific embodiments 1 to 9.
[0048] The following examples are used to verify the beneficial effects of the present invention:
[0049] Embodiment 1:
[0050] A method for preparing a porous carbon nanotube high thermal conductivity intermediate layer suitable for brazing is carried out according to the following steps:
[0051] 1. Using hydrothermal method to load carbon source:
[0052] ① Dissolve glucose in deionized water and stir evenly at room temperature to obtain a glucose solution;
[0053] The concentration of the glucose solution is 0.1 mol / L;
[0054] ② Immerse the copper foam in glucose solution and react at high temperature and high pressure for 6 hours at a reaction temperature of 180°C and a pressure of 5MPa;
[0055] The pore number per inch (PPI) of the foam copper is 95, and the diameter of the foam copper is 25 mm;
[0056] ③ After high temperature and high pressure reaction, cooling to room temperature, a foam copper loaded with carbon source is obtained;
[0057] 2. Annealing at high temperature:
[0058] Under the conditions of a protective atmosphere and a gas flow rate of 50 sccm, the temperature was raised to 550°C at a heating rate of 5°C / min, and then the carbon source-loaded copper foam was kept warm for 4 hours under the conditions of a protective atmosphere, a gas flow rate of 50 sccm and a temperature of 550°C, and finally taken out after being cooled in the furnace to obtain a porous high thermal conductivity intermediate layer of carbon nanotubes;
[0059] The protective atmosphere is argon.
[0060] Figure 1 This is a scanning electron microscope image of the porous high thermal conductivity middle layer of carbon nanotubes prepared in Example 1; it can be seen from the image that the carbon nanotubes are densely distributed on the foam copper skeleton, and there are granular balls at the roots of the carbon nanotubes, namely Cu nanoballs.
[0061] Figure 2 This is a transmission electron microscope spectrum of the nano copper ball catalytic array in the porous high thermal conductivity middle layer of carbon nanotubes prepared in Example 1; hydrothermal carbon is decomposed into a gas phase carbon source by heat, and then falls vertically and deposits in situ. According to EDS, Cu diffuses from the base material to the surface, and the Cu nano balls are evenly distributed, and the Cu nano balls are used as catalysts for the growth of carbon nanotubes.
[0062] Figure 3 This is a digital photo of the porous high thermal conductivity middle layer of carbon nanotubes prepared in Example 1. Since carbon has a strong absorption of photons, the appearance of this example is obviously black, and it fits well with the substrate and is evenly distributed.
[0063] Figure 4 This is an enhanced Raman curve of the carbon nanotube porous high thermal conductivity intermediate layer prepared in Example 1; as can be seen from the figure, the carbon peak is obvious, and it shows I due to the influence of the hydrothermal carbon retained on the substrate D >I G trend.
[0064] The thermal conductivity of the carbon nanotube porous high thermal conductivity middle layer prepared in Example 1 reaches 28 W / m·K, while the thermal conductivity of the original foam copper is only 13 W / m·K, which is nearly doubled.
Claims
1. A method for preparing a porous high thermal conductivity carbon nanotube intermediate layer suitable for brazing, characterized in that It is carried out in the following steps:
1. Using hydrothermal method to load carbon source: ① Dissolve glucose in deionized water and stir evenly at room temperature to obtain a glucose solution; ② Immerse the copper foam in glucose solution for high temperature and high pressure reaction; ③ After high temperature and high pressure reaction, cooling to room temperature, a foam copper loaded with carbon source is obtained; 2. Annealing at high temperature: Under the conditions of protective atmosphere and temperature of 550°C to 750°C, the foam copper loaded with the carbon source is kept warm for 4h to 5h, and finally taken out after being cooled in the furnace to obtain a porous high thermal conductivity middle layer of carbon nanotubes, thus completing the preparation method of the porous high thermal conductivity middle layer of carbon nanotubes suitable for brazing.
2. The method for preparing a porous carbon nanotube high thermal conductivity intermediate layer suitable for brazing according to claim 1, characterized in that The concentration of the glucose solution described in step 1① is 0.1 mol / L to 1 mol / L.
3. The method for preparing a porous carbon nanotube high thermal conductivity intermediate layer suitable for brazing according to claim 1, characterized in that The number of pores per inch (PPI) of the foam copper described in step 1② is 90 to 100.
4. The method for preparing a porous carbon nanotube high thermal conductivity intermediate layer suitable for brazing according to claim 1, characterized in that The high temperature and high pressure reaction described in step 1② is specifically carried out at a reaction temperature of 180°C to 200°C and a pressure of 5MPa to 10MPa for 3h to 6h.
5. The method for preparing a porous carbon nanotube high thermal conductivity intermediate layer suitable for brazing according to claim 1, characterized in that The high temperature and high pressure reaction described in step 1② is specifically carried out at a reaction temperature of 180°C to 200°C and a pressure of 5MPa to 10MPa for 6h.
6. The method for preparing a porous carbon nanotube high thermal conductivity intermediate layer suitable for brazing according to claim 1, characterized in that The protective atmosphere described in step 2 is one of argon, hydrogen and nitrogen or a mixed gas of several of them.
7. The method for preparing a porous carbon nanotube high thermal conductivity intermediate layer suitable for brazing according to claim 1, characterized in that The gas flow rate of the protective atmosphere described in step 2 is 50 sccm to 80 sccm.
8. The method for preparing a porous carbon nanotube high thermal conductivity intermediate layer suitable for brazing according to claim 1, characterized in that In step 2, under a protective atmosphere, the temperature of the carbon source loaded copper foam is raised to 550° C. to 750° C. at a heating rate of 5° C. / min to 15° C. / min.
9. The method for preparing a porous carbon nanotube high thermal conductivity intermediate layer suitable for brazing according to claim 1, characterized in that In step 2, under a protective atmosphere, the temperature of the carbon source loaded copper foam is raised to 600° C. to 750° C. at a heating rate of 5° C. / min to 10° C. / min.
10. The method for preparing a porous carbon nanotube high thermal conductivity intermediate layer suitable for brazing according to claim 1, characterized in that In step 2, the carbon source loaded copper foam is kept warm for 4 to 5 hours under a protective atmosphere and a temperature of 600° C. to 750° C.
Citation Information
Patent Citations
Supercapacitor carbon pipe / molybdenum carbide combination electrode material and preparation method thereof
CN106024403A
Carbon nanotube composite electrode material and preparation method thereof
CN113410063A
Enzyme-free glucose sensor electrode based on CuCo bimetal organic framework material as well as preparation and application of enzyme-free glucose sensor electrode
CN116068037A
Nitrogen-doped carbon nanotube-nickel-doped molybdenum nitride composite material and preparation method and application thereof
CN117966202A
Method for uniformly enhancing copper-based multi-channel heat-conducting interface material by three-dimensional graphite
CN118755985A